ANALISA KEHILANGAN PANAS SECARA KONDUKSI PADA SALURAN STEAM (PIPA) DARI TURBIN KE BACK PRESSURE VESSEL (BPV) PADA PABRIK KELAPA SAWIT (PKS) KAPASITAS 45 TON/JAM - Andika, Wahyu; Mulyara, Budi; Effendi, Zulham; Sembiring, Arifa Sura (Jurnal Agro Fabrica, 2023)
The Palm Oil Factory (PKS) is a factory that operates to process Fresh Fruit Bunches/FFB into several products, the main products of the palm oil factory are Crude Palm Oil (CPO) and Palm Kernel Oil (PKO). This research aims to measure temperature temperature in the distribution pipe between the turbine and the back pressure vessel which uses the observation method by observing directly. The results of this research show that on T1 on the first day the temperature was 161.5°C, on the second day there was a fairly low temperature drop at 142°C, on T2 it was not far from T1, on T3 there was a decrease in temperature in the boiler and at T4 there is a fairly low decrease and increase in temperature. Researcher Manarik concluded that a decrease in temperature between the distribution pipe between the turbine and the Back Pressure Vessel is a common occurrence in palm oil mills, and this can affect the operational efficiency and performance of the mill. Therefore, this research aims to determine the loss of heat energy. by conduction in the steam distribution pipe entitled "Analysis of Heat Loss by Conduction in the Steam Channel (Pipe) from the Turbine to the Back Pressure Vessel in a Palm Oil Mill (PKS) with a Capacity of 45 Tons/Hour"